Reactive ion etching of transition-metal alloys - Akinaga, Hiro (Animo Repository, 2006)
For production of advanced spin-electronic devices, such as a magnetic random access memory with the higher-density memory cell, a reactive ion etching (RIE) process of transition metal alloys is the indispensable component of development, while no transition-metal compounds with the relatively high vapor pressure have been founded so far. Here, we show the RIE process of a NiFe thin film by using CH4:O2:NH3 discharge. The RIE process was designed by ab initio calculations, and the present result is the first successful demonstration of the chemical effect in the RIE process for transition-metal alloys. The relative etching ratio of NiFe against Ti as the metal mask was decreased by substituting CH4 with CHF3.